Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan pada PT Japfa Comfeed Indonesia Tbk (2021-2023) - Neni, Laelis; Nurlela; Syahruni , Fitri (Cattleya Darmaya Fortuna, 2024)
The past Covid-19 period had a negative impact on the economy and business, in order to rise and advance its business again, PT Japfa Comfeed Indonesia Tbk continues to strive to create a wider marketplace and market reach, increase the number of consumers, and greater sales. Therefore, this quantitative descriptive research was conducted to analyze the financial performance of PT Japfa Comfeed Indonesia Tbk in 2021-2023. The data used is secondary data. The data collection method uses the documentation method. Analysis of financial statements using various financial ratio indicators such as liquidity ratio measured using current ratio and quick ratio, solvency ratio measured using debt to assets ratio and debt to equity ratio, and profitability ratio measured using return on assets and return on equity. The results of the analysis show that the company's financial performance is in the good category using the current ratio, quick ratio, and debt to assets ratio. However, the debt to equity ratio, return on assets, and return on equity need to be reviewed and improved to achieve the expected level of performance.